Multiple and Promising Applications of Strontium (Sr)-Containing Bioactive Glasses in Bone Tissue Engineering - Kargozar, Saeid; Montazerian, Maziar; Fiume, Elisa; Baino, Francesco (Frontiers in Bioengineering and Biotechnology, 2019)
Improving and accelerating bone repair still are partially unmet needs in bone regenerative therapies. In this regard, strontium (Sr)-containing bioactive glasses (BGs) are highly-promising materials to tackle this challenge.. The positive impacts of Sr on the osteogenesis makes it routinely used in the form of strontium ranelate (SR)) in the clinical setting, especially for patients suffering from osteoporosis. Therefore, a large number of silicate-, borate-, and phosphate-based BGs doped with Sr and produced in different shapes have been developed and characterized, in order to be used in the most advanced therapeutic strategies designed for the management of bone defects and injuries. Although the influence of Sr incorporation in the glass is debated regarding the obtained physicochemical and mechanical properties, the biological improvements have been found to be substantial both in vitro and in vivo. In the present study, we provide a comprehensive overview of Sr-containing glasses along with the current state of their clinical use. For this purpose, different types of Sr-doped BG systems are described, including composites, coatings and porous scaffolds, and their applications are discussed in the light of existing experimental data along with the significant challenges ahead.